A Retrospective Study Suggests 55 Days of Persistence of Sars-Cov-2 During the First Wave of the Pandemic in Santiago de Chile - Sandino-Garcia, A; Imarai-Bahamonde, C; Maisey-Munoz, K; Acuna-Castillo, C; Valdes-Henriquez, D; Leiva-Salcedo, D; Vidal-Palomo, M; Vidal-Palomo, M; Rojo-Castillo, L; Luraschi-Vargas, R; Barrera-Ávalos, C; Reyes-Lopez, F; et al. (Elsevier Ltd, 2024)
Background: As the COVID-19 pandemic persists, infections continue to surge globally. Presently, the most effective strategies to curb the disease and prevent outbreaks involve fostering immunity, promptly identifying positive cases, and ensuring their timely isolation. Notably, there are instances where the SARS-CoV-2 virus remains infectious even after patients have completed their quarantine. Objective: Understanding viral persistence post-quarantine is crucial as it could account for localized infection outbreaks. Therefore, studying and documenting such instances is vital for shaping future public health policies. Design: This study delves into a unique case of SARS-CoV-2 persistence in a 60-year-old female healthcare worker with a medical history of hypertension and hypothyroidism. The research spans 55 days, marking the duration between her initial and subsequent diagnosis during Chile s first COVID-19 wave, with the analysis conducted using RT-qPCR. Results: Genomic sequencing-based phylogenetic analysis revealed that the SARS-CoV-2 detected in both Nasopharyngeal swab samples (NPSs) was consistent with the 20B clade of the Nextstrain classification, even after a 55-day interval. Conclusion: This research underscores the need for heightened vigilance concerning cases of viral persistence. Such instances, albeit rare, might be pivotal in understanding sporadic infection outbreaks that occur post-quarantine. © 2024